A Case Study on Recycling Industrial Wastewater with Nanofiltration Membrane Separation Technology - Yiqiang Deng; Xiaoqian Bai; Jialong Lin; Linyan Yang; Yuqing Lin; Mingyue Lin; Guangli Xiu (Membranes)
As pressure on water resources intensifies and stringent regulations for groundwater and surface water are enacted, wastewater recycling has emerged as a key research objective for many enterprises. In this study, based on the actual wastewater discharged from Eternal Electronic (Suzhou, China) Co., Ltd., the performance differences in different membrane materials in treating this wastewater were analyzed and compared. The NF90 membrane was ultimately selected as the most suitable choice for treating this wastewater with optimal operating conditions of 150 psi, 25 °C, and 1 L/min, respectively. All the indices of wastewater treatment can satisfy the standard of circulating cooling water. In addition, this work is closely combined with the practical applications by using an HCl solution (pH = 3–4) to clean the fouled membranes, thus effectively solving the membrane fouling in the treatment process. This approach not only satisfies the environmental management requirements of enterprises but also provides valuable insights for similar wastewater treatment projects.